EDUKASI MODERASI BERAGAMA MELALUI SUB-CPMK AGAMA KATOLIK KEBAJIKAN BIBLIS DENGAN METODE PjBL DI PERGURUAN TINGGI - Hayon, Vinsensius (Pastoralia Jurnal Penelitian Dosen, 2024)
The acceleration of progress in the field of Science and Technology (Science and Technology) can be felt and has unlimited effects in various areas of life. All progress movements are covered in and within the realm of globalization mobility and the domain of Industrial Revolution 4.0. The effect is very pronounced and its influence penetrates very quickly into the realm of education, thus influencing the attitude of life of students as a young generation. In connection with relations and interactions between students and between religious communities, great efforts are made to construct an understanding of moderate religious practices so as not to fall into radical and exclusive, extreme and intolerant positions. Therefore, "biblical virtues" are taught and internalized through the Catholic Religion Sub-CPMK as a basis for being moderate in life between religious brothers. The purpose of writing is to discuss Biblical Virtue as the basis for a moderate attitude to be manifested and become a life guide that has been started to knit fraternity between students in higher education, so the PjBL method is the means and the approach used is SCL. The writing method used is library research. The conclusion of this study is that in multi-religious life a basis is needed as a guide and guide to form a moderate attitude and it is manifested in the practice of life between religious adherents, so that a moderate attitude is grounded in interacting with anyone without prejudice. Religious moderation requires various attitudes in the form of recognition of the existence of other parties, tolerance, respect for differences in religious beliefs and not imposing one's will in violent, extreme and radical ways. The PjBL method is one of the strategies to provide understanding that the source of moderation is Biblical Virtue. Sub-CPMK space for deepening and practicing moderate attitudes that are based on and lead to social interactions both internally and externally empowered for peace and harmony in life.